2016
DOI: 10.1186/s13000-016-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

DEF6 expression in ovarian carcinoma correlates with poor patient survival

Abstract: BackgroundIncreased expression of DEF6 is correlated with the malignant behavior of various cancers. Both DEF6 and p16 contribute to the regulation of cell cycle progression, and p53 plays important role in the cell cycle checkpoints. This study was designed to elucidate the prognostic significance of DEF6, p53 and p16 immunoexpressions in different histology subtypes of ovarian carcinoma.MethodsImmunohistochemistry results of DEF6, p53 and p16 on ovarian carcinoma were compared with histology subtypes, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…From the years 1999 to 2013, totally 94 patients including 27 mucinous ovarian adenomas, 38 MuOCs and 29 SeOCs were retrieved from the archival pathology files of the Taipei Medical University 35 and Taipei Medical University Joint Biobank. The hematoxylin and eosin-stained slides were reviewed by two pathologists, and representative blocks with whole tissue sections of ovarian tumors were selected for immunohistochemistry (Supporting Information, Table S4).…”
Section: Study Participants Tissue Sections Tissue Microarray and Imentioning
confidence: 99%
“…From the years 1999 to 2013, totally 94 patients including 27 mucinous ovarian adenomas, 38 MuOCs and 29 SeOCs were retrieved from the archival pathology files of the Taipei Medical University 35 and Taipei Medical University Joint Biobank. The hematoxylin and eosin-stained slides were reviewed by two pathologists, and representative blocks with whole tissue sections of ovarian tumors were selected for immunohistochemistry (Supporting Information, Table S4).…”
Section: Study Participants Tissue Sections Tissue Microarray and Imentioning
confidence: 99%
“…However, a robust biomarker for predicting metastasis and prognosis in patients with OS does not exist (37). Accumulating evidence suggests that in various types of cancer, such as ovarian carcinoma and colorectal cancer, DEF6 is associated with disease progression and poor prognosis (12,(17)(18)(19)(20). In the present study, the results demonstrated that DEF6 was widely expressed in human OS tissues and that its accumulation was positively correlated with advanced Enneking stage and distant metastases.…”
Section: Discussionmentioning
confidence: 47%
“…DEF6, also known as IBP, is a pivotal driver responsible for regulating immune cell biology and autoimmunity, and has been frequently been reported to be amplified in several types of cancer (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The results of the current study determined whether DEF6 is a novel oncogene in OS.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations